Metodologi Pemahaman Hadis M. Yusuf al-Qaradhawi: Studi Analitis Atas Hadis Partisipasi Wanita Dalam Berpolitik - Choiroh, Wahyuni Nuryatul; Munawir, Munawir (Al-Qudwah, 2023)
Sunni scholars view Hadith as a normative source capable of embodying the essence of the Qur'an, considering Hadith's position as the second source of Islamic religious teachings after the Qur'an. The controversy between textual and contextual schools of thought regarding the study of Hadith has existed since the early development of Islam. Even to this day, textualist scholars continue to advocate for their principles. This study aims to uncover Yusuf al-Qaradhawi's thoughts on the methodology of understanding Hadith in his book "Kaifa Nata’amal ma’a al-Sunnah al-Nabawiyah" (How to Interact with the Prophetic Sunnah), enabling scholars of Hadith to understand Hadith properly. In this context, the author raises the issue of women's participation in politics as an implication of the offered methodology. This research adopts a qualitative approach with a library research method. The results of this study indicate that al-Qaradhawi proposes eight basic principles for understanding the Hadith of the Prophet Muhammad (peace be upon him). These principles include understanding Hadith in harmony with the Qur'an, combining several Hadiths on one topic, reconciling conflicting Hadiths, understanding Hadiths in their background, situation, and orientation, distinguishing between the inconsistency of the means and the consistency of the objectives of the Hadith, comparing literal and metaphorical expressions in understanding Hadiths, comparing the unseen with the visible, and validating the terminology of Hadith. The methodological framework proposed by al-Qaradhawi is expected to keep the study of Hadith relevant to the changing times. Regarding the implications and significance of his methodology regarding women's participation in politics through Hadith, it can be concluded that, according to al-Qaradhawi, women have the same rights to participate and engage in politics as men.  Abstrak: Ulama sunni memandang hadis sebagai sumber normatif yang dapat mengejawantahkan esensi al-Qur'an,  mengingat posisi hadis sebagai sumber ajaran agama Islam kedua setelah al-Qur'an. Adanya kontroversi antara mazhab tekstual dan kontekstual terhadap kajian hadis, sejatinya telah ada semenjak awal Islam berkembang. Bahkan hingga masa kini, kaum tekstualis masih memiliki eksistensi untuk menggaungkan prinsipnya. Penelitian ini bertujuan untuk menyingkap pemikiran Yusuf al-Qaradhawi terkait metodologi pemahaman hadis dalam kitabnya Kaifa Nata’amal ma’a al-Sunnah al-Nabawiyah (bagaimana berinteraksi dengan hadis Nabi) bagi para pengkaji hadis untuk dapat memahami hadis secara baik dan benar. Dalam hal ini penulis mengangkat tentang hadis partisipasi wanita dalam berpolitik sebagai implikasi dari metodologi yang ditawarkan. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kepustakaan (library research). Hasil dari penelitian ini menunjukkan bahwa al-Qaradhawi menawarkan delapan asas dasar dalam memahami hadis Rasulullah Saw, yaitu pemahaman hadis selaras dengan Al-Quran, penggabungan beberapa hadis dalam satu topik, penggabungan atau mentarjih hadis yang  kontradiktif, pemahaman hadis dengan tinjauan latar belakang, situasi kondisi dan orientasi hadis, pemilahan antara inkonsistensi sarana dan konsistensi sasaran hadis, perbandingan antara ungkapan haqiqi dengan majazi dalam pemahaman hadis, perbandingan antara ghaib dengan yang nyata,  dan validasi kaidah terminologi hadis. Tawaran metodologi yang dikemukakan oleh al-Qaradhawi diharapkan membuat kajian hadis tetap relevan dengan perkembangan zaman. Terkait implikasi dan signifikansi dari metodologinya melalui hadis partisipasi wanita dalam berpolitik, secara umum dapat ditarik kesimpulan bahwa menurut al-Qaradhawi, seorang wanita memiliki hak yang sama untuk berpartisipasi dan berkiprah dalam dunia politik layaknya seorang laki-laki.